Effect of β-sitosterol against methyl nitrosourea-induced mammary gland carcinoma in albino rats. Issue 1 (December 2016) - Manral, Chetan; Roy, Subhadeep; Singh, Manjari; Gautam, Swetlana; Yadav, Rajnish; Rawat, Jitendra; Devi, Uma; Ansari, Md; Saeedan, Abdulaziz; Kaithwas, Gaurav
Abstract Background The present study was in quested to study the effects of β-sitosterol on methyl nitrosourea (MNU) induced mammary gland carcinoma in albino wistar rats. Methods Animals were randomized and divided into four groups of eight animals each. Group I (sham control 1 % CMC in normal saline p.o.); Group II (toxic control, MNU 47 mg/kg, i.v); Group III (MNU 47 mg/kg, i.v + β-sitosterol, 10 mg/kg, p.o); Group IV (MNU 47 mg/kg, i.v + β-sitosterol, 20 mg/kg, p.o). Toxicity was induced by single i.v. injection of MNU followed by β-sitosterol supplementation therapy for 115 days at the dose mentioned above. Results Treatment with β-sitosterol evidenced decrease in the alveolar bud and lobule score in the whole mount of the mammary gland. β-sitosterol exhibited diminishing effect on oxidative stress through synchronizing lipid and enzymatic antioxidant defense. A significant decrease in the saturated and unsaturated fatty acid was evident with the MNU treatment and β-sitosterol demonstrated a marked effect on it. Pgp 9.5 expression was dose dependently upregulated by β-sitosterol treatment in comparison to MNU treatment. On the contrary, downregulated NF-kB expression was perceived, when β-sitosterol was concomitantly administered with MNU. Conclusion β-sitosterol afforded significant protection against the deleterious effects of MNU.